Pengaruh Kesadaran Wajib Pajak, E-Samsat dan Sanksi Terhadap Penerimaan Pajak Kendaraan Bermotor - Puji Rahayu (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2023)
This study aims to determine the effect of taxpayer awareness, E-samsat and sanctions on motor vehicle tax revenue. This research was conducted at the Joint Office of Samsat II (Katang) Kediri Regency. The sampling technique used in this study is incidental sampling. The sample used in this study amounted to 100 respondents. The data analysis technique used is multiple linear regression analysis. The results of this study indicate that taxpayer awareness affects motor vehicle tax revenue, E-samsat influences motor vehicle tax revenue, sanctions affect motor vehicle tax revenue, and taxpayer awareness, E-samsat and sanctions influence simultaneously (together) on motor vehicle tax revenue. This is known based on the results of the F test as follows: a significance value of 0.000 <0.05 and 0.000 <0.05 and an R Square value of 0.402 or 40.2% and 0.467 or 46.7% which means that the taxpayer awareness variable , service quality and sanctions have a simultaneous effect (together) on motor vehicle tax revenues of 40.2% and 46.7%.